HASHİMOTO TİROİDİTİ HASTALIĞINDA SONOGRAFİK SHEAR WAVE ELASTOGRAFİ VE REZİSTİF İNDEKS DEĞERLERİ - ASLAN, HASAN (Fırat Üniveristesi, 2020)
Hashimoto Tiroiditi toplumda en sık görülen otoimmün hastalıkların başında gelmektedir. Bu çalışmada amacımız Hashimoto Tiroiditli hastalarda elastografi ve rezistif indeks (RI) değerlerini normal grupla karşılaştırarak tanıya katkısını araştırmaktır. Çalışmamıza 03.03.2018-25.02.2020 tarihleri arasında, klinik, laboratuar, radyolojik olarak Hashimoto tiroiditi tanısı alan 170 olgu ve sonografik laboratuvar incelemeleri normal olan 27 gönüllü katılımcı kabul edildi. Tüm olgulara gri-skala ultrasonografi, doppler, sonoelastografi incelemeleri yapıldı. Tüm katılımcılarda tiroid bezi sağ ve sol lobdan 3'er defa olmak üzere toplam 6'şar kez shear wave elastografi (SWE) ve her bir lobdan 1'er defada RI ölçümleri gerçekleştirildi. Çalışmaya katılım kriterlerini sağlayan 145'i vaka grubu ve 27'si kontrol grubu olmak üzere 172 katılımcı dahil edildi. Katılım kriterlerini sağlamayan 25 olgu çalışma dışında bırakıldı. Vaka grubunun elastografi ortanca değeri 2,33 m/s, kontrol grubunda ise 1,615 m/s olarak ölçülmüş olup, vaka grubunda anlamlı şekilde yüksek bulundu (p<0,001). Vaka grubunda elastografi değeri üzerinden yapılan ROC analizine göre katof değeri 1,85 olarak bulundu. Bu kesme noktadaki duyarlılık %83,45, özgüllük ise %81,48 olarak bulundu. Pozitif prediktif değer %96,03 olarak, negatif prediktif değer %47,83 ve doğruluk ise %83,76 olarak hesaplandı. Vaka ve kontrol grubu arasında RI değerleri açısından anlamlı bir fark bulunamadı (p=0,776). Hasta grubunda sonografik ekojeniteye göre 4 sınıf oluşturulduğunda sınıflar arasında ekojenite azaldıkça elastografi ve RI değerlerinde istatistiksel olarak anlamlı bir artış saptandı (p<0,05). Sonuç olarak Hashimoto tiroiditi tanısında ve takibinde, fibrozisin non invaziv olarak değerlendirilmesinde gri-skala ultrasonografik incelemeye renkli doppler ultrasonografik inceleme parametresi olan RI ölçümleri ve kantitatif sonuç veren SWE tekniğinin eklenmesinin tanı duyarlılığını oldukça artıracağını düşünmekteyiz. Anahtar Kelimeler: Hashimoto tiroiditi, shear wave elastografi, doppler ultrasonografi, rezistif indeks

Hashimoto's thyroiditis is one of the leading autoimmunity diseases most frequently seen in the population. The aim of the study is to investigate the contribution of elastography and resistive index (RI) values to the diagnosis in patients with Hashimoto's thyroiditis by comparing them with the normal group. 170 cases diagnosed with Hashimoto's thyroiditis in terms of clinical, laboratory and radiology tests and 27 volunteer participants who had normal sonographic-laboratory examinations between 03.03.2018-25.02.2020 were included in our study. Grey scale ultrasonography, doppler, sonoelastrography examinations were performed for all cases. In all participants, shear wave elastography (SWE) was measured in the thyroid glands, 3 times each in the right and left lobes, with a total of 6 times each and RI were measured once in each lobe. 172 participants, 145 being the case group and 27 being the control group fulfilling the inclusion criteria were included in the study. 25 cases not meeting the inclusion criteria were excluded from the study. The elastography median value was found as 2.33 m/s for the case group whereas it was measured 1.615 m/s for the control group. It was found significantly higher in the case group (p<0,001). According to the ROC analysis carried out through the elastography values in the case group, the cut off value was found as 1.85. In this cutting point, the sensitivity was found as 83.45% and the specificity as 81.48%. Positive predictive value was calculated as 96.03%, negative predictive value as 47.83% and accuracy as 83.76%. There was not a significant difference in RI values between the case and control groups (p=0,776). When 4 classes are formed according to the sonographic echogenicity in the patient group, a statistically significant increase in elastography and RI values was found as the echogenicity decreased (p< 0.05). In conclusion, it is believed that including RI measurements of a color doppler ultrasonographic examination parameter and the SWE technique providing quantitative results during the grey scale ultrasonographic examinations will considerably increase diagnostic sensitivity in terms of the diagnosis and follow-up of Hashimoto's thyroiditis. Keywords: Hashimoto's thyroiditis, shear wave elastography, doppler ultrasonography, resistive index
Sonographic shear-wave elastography and ri values in hashimoto's thyroiditis disease
Keywords: Radyoloji ve Nükleer Tıp